Age-associated changes in intestinal health biomarkers in dogs - Fernández-Pinteño, Anna; Pilla, Rachel; Manteca, Xavier; Suchodolski, Jan; Torre, Celina; Salas-Mani, Anna (Frontiers in Veterinary Science, 2023)
The gut microbiome is critical in maintaining the health of the host. In healthy humans, the aging process is one of the main factors modulating the changes in the intestinal microbiota. However, little is known about the relation between gut health, the microbiota and the aging process in dogs. The present work aims to explore the differences in the intestinal microbiota and the intestinal health based on fecal biomarkers in a population of dogs of different ages. The study involved 106 dogs of different breeds aged between 0.2 and 15 years old, categorized as senior (>7-year; n = 40), adult (2–7-year; n = 50) and junior (< 2-year; n=16). Fecal samples were collected during the same period at the same facilities. The analysis included the following gut health indicators: 16S rRNA gene sequencing to investigate the differences in the fecal microbiota, qPCR to determine the Dysbiosis Index, fecal short-chain fatty acids concentrations, fecal calprotectin and immunoglobulin A. Beta diversity analysis revealed a significant difference with small effect size (p = 0.003; R = 0.087) between age categories based on unweighted Unifrac, but no significance was observed based on weighted Unifrac metric or Bray-Curtis distances. There were no significant differences in the alpha diversity measures or on the fecal dysbiosis index between age categories. Senior dogs had significantly higher relative abundance proportions in phyla Bacteroidota and Pseudomonadota, and genera Faecalibacterium but not on qPCR analysis. At family level, Ruminococcaceae, Uncl. Clostridiales.1, Veillonellaceae, Prevotellaceae, Succinivibrionaceae and Bacteroidaceae abundances were higher in the senior category when compared to the adult and/or the junior categories. Relative proportions, but not concentrations of fecal acetate were higher in seniors, while, butyrate, isovaleric acid and valeric acid were lower. Valeric acid concentration was significantly lower in seniors than in adults. Calprotectin and immunoglobulin A levels did not differ significantly across groups. In conclusion, this study suggests multiple minor changes in the composition of the fecal microbiota and the relative amount of short-chain fatty acids in dogs between different age groups, but studies in larger populations representative of all the ages are warranted to refine the present results.